FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR - Mardiana, Annisa; Wijaya, Henryanto (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This research aims to determine the effect of profitability, likuidity, and firm size on firm value in manufacturing company listed on the Indonesia Stock Exchange in 2017 – 2019. The sample was selected by purposive sampling method and the valid data were 75 companies. The data processing technique uses multiple regression analysis assisted by Software Eviews version 11.0. The results of this study indicate that profitability, liquidity and firm size have no effect on firm value. The implication of this research is if small assets are used optimally with optimal sales and cost efficiency, the company will still be able to maintain company value, as well as for companies that have large assets.